Prediction of the length and width of quail eggs using linear regression analysis - Alasahan, Sema; Hark, Betül Dağoğlu; Eltas, Ömer (My University, 2019)
Aim: This study was aimed at establishing regression equationsfor the estimation of egg length and egg width valuesusing egg weight values in quail eggs, and at determining theerror rate of the regression equations established.Materials and Methods: Quail eggs were collected twice,between June and August to be used for the establishment ofequations, and between September and October to be usedfor the assessment of the accuracy of the equations established.The numeric measurements of the eggs are presented asmeans and standard deviations.Results: Equations were established for the estimation ofthe dependent egg length and egg width variables usingthe independent egg weight variable with linear regressionanalysis. It was determined that equations (1) and (2) establishedfor the estimation of egg length and egg width, respectively,both performed very well. The R² value was 0.99for both equations, which demonstrated that the egg weightvariable had a share of 99% in describing the total change inthe egg length and egg width variables. The mean differencebetween the regression equation established in this studyfor the estimation of egg length and the Rahn and Paganelli(1988) equation was found to be statistically insignificant(P=0.939).Conclusion: In result, the regression equation established inthis study for the estimation of quail egg width was ascertainedto perform better than the Rahn and Paganelli (1988)equation, and the mean difference between these two equationswas statistically significant.
Keywords: Matematik; Gıda Bilimi ve Teknolojisi; Veterinerlik; İstatistik ve Olasılık